Severe facial reaction to thiurams in surgeons - Luca Coppeta; Francesca Papa; Antonio Pietroiusti; Ludovico Maria De Zordo; Stefano Perrone; Silvia Barone; Andrea Magrini (Nofer Institute of Occupational Medicine, 2019)
Contact dermatitis is a major problem in the healthcare environment and in other sectors. Healthcare professionals may be exposed to a large number of chemical agents, including the accelerators for rubber vulcanization process. The prevalence of allergic contact dermatitis among operators in the sector ranges 13-30%. This paper describes the case of a 46-year-old male cardiac surgeon affected by a severe skin reaction localized on the face in the absence of hand dermatitis, presumably resulting from the use of a surgical patch applied to the face. Patch tests were performed and the result was negative for latex and positive (+++) for thiuram mix. A thiuram-free tape was prescribed and the operator's dermatitis improved significantly. Thus, it would be very important to pay attention to skin disorders in health workers and thiuram as an occupational allergen. Med Pr. 2019;70(1):121-4